Investigation of Cutter–Woodchip Contact Pressure in a New Biomass Comminution System - Lin, Lianshan; Lanning, David; Keiser, James R.; Qu, Jun (Frontiers in Energy Research, 2022)
A Crumbler® rotary shear system was recently developed to process fuel-grade woodchips into feedstocks having more uniform particle sizes for improved flowability and higher thermochemical output yield than a traditional hammer mill. It represents a significant innovation in the state of the art of biomass comminution equipment. However, the milling unit has experienced significant abrasive wear of the feeding teeth and cutters when processing hard and dusty feedstocks, such as logging residue and corn stover. Here, we present initial simulation results from a finite-element stress analysis of the rotary shear, which is used to investigate the dynamics of interaction between the cutters and woodchips. This is the first step for optimizing the cutter design to improve the system lifetime and processing efficiency, thus reducing downtime and improving overall productivity.